In-situ pyrolysis mining theory and technical conception of controllable and spontaneous combustion of tar-rich coal - Jun DENG; Junhui LU; Shuangming WANG; Kai WANG; Qiang SUN; Caiping WANG; Qingmin SHI; Jishi GENG; Jinrui WANG; Chang SU; Gaoyang QU (Meitan xuebao)
As a strategic coal-based oil and gas resource, tar-rich coal is abundant in China. The development of oil and gas resources rich in oil and coal is of great strategic value to ensure China’s energy security and help the “double carbon” goal and energy transformation. Underground in-situ pyrolysis extraction of oil and gas is one of the important ways for low-carbon green development and efficient utilization of tar-rich coal. Using the spontaneous combustion of pyrolysis semi-coke as the heat source of in-situ pyrolysis can improve the efficiency of tar-rich coal resource exploitation, but it is necessary to focus on breaking through the problems of controllable spontaneous combustion of pyrolysis semi-coke, efficient mass and heat transfer, reliable geological guarantee system and controllable underground environmental pollution. The scientific and technological conception of in-situ pyrolysis mining of controllable and spontaneous combustion of tar-rich coal is expounded. The mechanical theory of mining rock mass, the theory of controllable and spontaneous combustion of pyrolysis semi-coke, the visualization theory of “four fields” and the theory of multi-physical field coupling heat transfer are put forward. The coupling damage mechanism of underground coal and surrounding rock under mining disturbance, the exothermic characteristics and controllable conditions of spontaneous combustion of pyrolysis semi-coke, the mechanical behavior and energy evolution characteristics of multi-physical field coupling rock mass are revealed, which provides a theoretical basis for the construction of in-situ pyrolysis mining technology system of controllable and spontaneous combustion of tar-rich coal. For the key links in the mining technology, the pyrolysis semi-coke controlled spontaneous combustion technology, in-situ mass and heat transfer enhancement technology, underground closed system technology and in-situ mining geological guarantee technology were established, which provided technical support for the in-situ pyrolysis mining of tar-rich coal controlled spontaneous combustion. On this basis, the in-situ pyrolysis mining theory and technology system of controllable and spontaneous combustion of tar-rich coal was constructed, the difficulties and key points of future research were clarified, and the technical path and research direction of high-efficiency, low-carbon and safe development engineering, industrialization and scale of tar-rich coal in China were put forward.